Characterization and bioactivity of nanoemulsions from Leucaena leucocephala and Annona muricata extracts against Spodoptera frugiperda - Nuryanti, Ni Siluh Putu; Maulida, Desi; Ardiansyah, Sigit; Pratiwi, Nurma; Dulbari, Dulbari (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Spodoptera frugiperda is a major pest that attacks food and horticultural crops. The development of botanical pesticides in nanoemulsion form is one strategy to manage this pest. This research aimed to analyse the properties and effectiveness of nanoemulsions formulated using phase inversion and homogenization methods from Leucaena leucocephala and Annona muricata seed extracts against S. frugiperda. The research methods included mass rearing of S. frugiperda, extraction of L. leucocephala and A. muricata seeds, nanoemulsion formulation, and characterization of nanoemulsion properties. The results showed that the phase inversion method produced larger particle sizes compared to the homogenization method. Similarly, the phase inversion method resulted in a wider particle size distribution, while homogenization produced more uniform droplets. The nanoemulsion of the mixed extract of L. leucocephala and A. muricata seeds formulated using the homogenization method provided an antifeedant effect of 56.15% (medium inhibition criteria). The lowest antifeedant activity was observed in nanoemulsion from L. leucocephala using the phase inversion method (36.87%, low inhibition criteria). The highest ovicidal effect (72.93%) was also obtained from the mixed-seed nanoemulsion prepared by homogenization.